Comparisons of Different Composts and Growing Substrates on Growth and Productivity of Lettuce (Lactuca sativa) - Sitthivohane, Insavai; Lattanasouvannaphon, Champa; Chathaokalor , Daovang; Phommachak , Thavivanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Currently, compost is widely known and used for organic agriculture production. which was conducted from using agricultural rare material and kitchen wastes to ferment through the biological process and appropriate temperature, and primary base on organic agriculture production (Luis F DiaZ, 2011), the concept of compost was initiated due to long term effect using remaining chemical pollutants that has become a critical challenge and academic are now finding ways to tackle this problem, the compost has a property in soil structure improvement, there are multiple of nutrients and it was being a residence of living micro-organism, it improves agriculture cultivation and clean agriculture production, to ensure the food safety and become eco-friendly. The high quality compost can be easily produced based on natural material utilization, which would be utilized the high economic potential by natural resource. Hence, the main factor of growing plants a part from watering composts has significant role in the garden. Moreover; this study will help the farmers to select the right compost and producing multiple composts to increase their own productivity. Because of the reason of this study focused on Comparisons of Different Composts and Growing Substrates on Growth and Productivity of Lettuce. This experimental design was carried out in Living Land Community Farm, Luang Prabang city and province, which complemented in 2nd September – 15 October 2018, through the use of Randomized Completed Block Design (RCBD), growing and productive data were collected including height of stem, width of leaves, length of leaves, amount of leaves, weigh in gram/plant and weight in kilogram/square meters, program Sirichai Statistics 6.07 has been used for analysis. The result indicated that Living land compost has the largest number of height which was provided 10.46 cm. At the same time, other treatment presented ordering number as 9.99 cm, 9.72, 9.55, 8.79 cm. Whatever, the width of lettuce has been changed rapidly, Land fill compost + buffalo’s dung has the highest width of lettuce leaves presented 3.31 cm and other treatment was presented as 3.26 cm, 3.23 cm, 3.14 cm, 3.11 cm. On the other hand, Land fill compost + buffalo’s dung had also provided the largest number of Length, it distributed 7.86 cm, for other treatments had an indicator as 7.68 cm, 7.56 cm, 7.42 cm, and 7.14 cm. In addition, amount of lettuce leaves has been changed rapidly, Living land compost has the huge number of amount which provided 14.67 leaves, while the other treatment provided only 14.19 cm, 13.63 cm, 13.27 cm, 11.57 cm. As the result of productivity of lettuce, Living land compost 5 kg/m2 = 15 kg /bed provided 1.13 kg/m2. In following number, Landfill compost 2 kg/m2 + buffalo dung 3 kg/m2 = 15 kg/bed presented 1.08 kg/m2. At this time, Landfill compost 2 kg/m2 + Job’s tear bark 3 kg/m2 = 15 kg/bed indicated 1.06 kg/m2. Then, Landfill compost 2 kg/m2 + garden wastes 3 kg/m2 = 15 kg/bed represented 1.04 kg/m2 and Landfill compost 5 kg/m2 = 15 kg /bed (control) provided least of productivity only 1.00 kg/m2.